Annual Plan 2000-2001 Volume I (Part II) Uttar Pradesh - Planning Commission (Planning Commission, 2000)
Uttar Pradesh occupies 9% of the total Geographical area and 16% of the country's population. Of the total 29.79 million hectare reporting area of the State, the net cropped area is only 17.51 million ha., of which 69% is Irrigated. Seventy two percent of total work force (1990-91) is dependent on Agriculture of which 19 percent are landless agricultural labourers. There is a preponderance of small and marginal farmers in the State. Comprising 90% of the total farmers, however these groups own only 24% and 31 % of the land area respectively. The process of fragmentation of holding is still continuing & there is a continues increase in the number of marginal farmers. During one decade (1980-81 to 1990-91) the number of marginal farmers increased by 17.7%. The average size of holding in the State is 0.90 ha. The State has highly heterogeneous agro-climatic conditions ranging from temperate sub Himalayan -mountainous terrain to dry & hot rainfed semi arid conditions of Bundelkhand and plateau area of Mirzapur & Allahabad. On the other hand there are waterlogged/high ground water area of eastern U.P.
Government of Uttar Pradesh State Planning Commission